PAGANA MERANAO: A Royal Feast as an Institution - Pimping, Cadidia (JPAIR Multidisciplinary Research, 2013)
The study aimed to describe its origin, historical and other components in the preparation of Meranao foods. Specifically, the research work pursued the following objectives. 1) To describe the Meranao decorations during the Pagana Meranao, 2) To describe the Pagana Meranao food preparation and serving, 3) To describe the Pagana Meranao as royal entertainment. The study used the descriptive design involving qualitative techniques, supported by interviews to key informants who are knowledgeable about the tradition and customs of the Meranao. The study utilized all available Meranao materials references on Pagana Meranao found in the library to counter check information given by key informants for better understanding of the research work and its significance, especially the non-Meranaos. The researcher also conducted an actual observation about the serving of Pagana Meranao.